Statistical literacy, reasoning and thinking: Specific competences that need to be promoted in classroom - Aguilar Fernández, Eduardo; Zamora Araya, José Andrey; Guillén Oviedo, Helen Susana (IE Revista de Investigación Educativa de la REDIECH, 2021)
The main objective of this essay is to analyze how the competencies approach can contribute to fulfilling the goals of statistics education. A revision about the concept of competencies, their types and approach is performed. Additionally, the relationship between competencies and Statistics education, along with the way to incorporate literacy, reasoning, and statistical thinking as competencies to be developed in class is analyzed. Besides, definitions are given about mathematics and statistics competencies emphasizing that although they complement each other, are different. Finally, recommendations and suggestions of the Guidelines for Assessment and Instruction in Statistics Education (GAISE) report are given for teaching statistics and how they could be applied in the classrooms under a competencies approach.